Development of Powtoon-Based Video Learning Media on Understanding Angles and Various Angles - Hidayat, Deri; Yuyun Elizabeth Patras; Hari Susanto, Lutfy (Journal of International Multidisciplinary Research, 2025)
Research on the development of PowToon-based video learning media on the material on the definition of angles and various angles. The purpose is to discover the development of Powtoon-based video learning media and the feasibility of Powtoon-based video learning media developed for grade III students of SDN Singajaya 01 through the learning process carried out at school. The method used in this study is the ADDIE method which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. In this study, a validation test was carried out on experts, namely media, language experts, and material experts. The results of the validation of media experts obtained as many as 96% with very feasible criteria. The results of the validation of the language experts obtained 100% with the feasible criteria, and the results of the validation of the material experts obtained 90% with very feasible criteria. The results of the student response questionnaire obtained as much as 92% with very feasible criteria. These results show that powtoon-based video learning media on the understanding of angles and various angles has proven to be valid, interesting, innovative and very feasible to be used in the learning process. This study recommends the development of PowToon-based video learning media that can be used in classroom learning.